Correlation of Age, Gender, and Body Mass Index With NLR of Covid-19 Patients - Novianti Novianti; Andra Novitasari; Ika Dyah Kurniati (Sean Institute, 2025)
The inflammatory and immunological responses may be used to predict the outcome of COVID-19 patients. The NLR may be used as an indicator of the severity of systemic inflammation in patients with viral pneumonia (NLR). NLR is linked to age-related immunosenescence Sex , and NLR, is a hormonally mediated trait. The prevalence of NLR is higher in people with COVID-19 who are overweight or obese. The researchers wanted to see how factors including age, gender, and BMI affected the NLR of people with COVID-19. This researched used Cross Sectional approach. A sample of 70 respondents with COVID-19 confirmed through RT-PCR examination at Dedy Jaya Hospital Brebes period January-August 2022. Statistical analysis to determine the correlation between variables using Spearman's non-parametric. From 70 samples of COVID-19 patients , the results of the analysis showed that the correlation between NLR and age had ap value = 0.001 with r = 0.558, the correlation between NLR and gender had ap value = 0.001 with r = 0.461 .